IMPLEMENTASI APLIKASI PHOTO EDITOR BERBASIS ANDROID UNTUK DESAIN WEBSITE - Akhmad Budi, (Jurnal Informatika dan Bisnis, 2017)
Information and communication technology is a rapidly growing technology. Developments that occur such as shifting the use of desktop PC to a laptop that is more portable. The development did not stop there, because then came the smaller, lighter device can even be stored in the pocket. This developments is also supported by rapid internet penetration. Therefore, this research has been overshadowed by the problems in website interfaces design on a smartphone. Website interface design on a smartphone takes a smaller image size than that on a PC or laptop. In conducting the study, researchers used a wide variety of theories that are used as reference, researchers also performed surgery on a photo editor application that already exist, such as the photo editor aviary, momentcam, camera 360, and others. In making this application the researchers used the language natively on Android platform, the Java programming language support. In conducting the study, researchers conducted observations indirectly, where researchers do not fall directly into the field to get data or indirectly distributing questionnaires, but the researchers collected data by conducting a review on the opinion of some people regarding the application of photo editor on the website, and through the literature on books, e-books, journals, and websites that have been approved. Through a process of research that has researchers run and the application development process that has taken place, the researchers concluded that the application of the researchers is derived from this study is an application of photo editor that can be easy to understand and use, and application of photo editor generated can also shrink the large sizes the image becomes smaller so that it can be used on the website on a smartphone. The conclusion of this study is the photo editor application can be used to resize the image, so that the images can be used in designing the interface on the website on a smartphone that makes the image can be displayed on a smartphone because it has a smaller size.Keywords : Android, Photo editor, Application, Website Design